BIOGRAFI DOKTER ABDUL RIVAI DI BENGKULU 1871-1933 - Andrizal Samidtro; Bedriati Ibrahim; Bunari S Bunari S (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Doctor Abdul Rivai was the first Indonesian to achieve a doctor’s degree in Netherlands. He is the actor Mukomuko district of Bengkulu Province. Doctor Abdul Rivai has a role in education, pers and healthy. Therefore, the purpose of this research is to know the figure of Doctor Rivai in this life. To know biography, the role done, to know where he did the role and appreciation he got. The method used in this research is qualitative. The data obtained from the interviews and the analyzed with their own language. While the location of the research is in Bengkulu city. This research started from the beginning of the tittle of research submitted until this thesis is completed. Data collection techniques and literature techniques. The results showed that study Doctor Rivai have a very important role in advancing the Indonesian nation generally, especially in Bengkuluto oppose the Dutch colonialism with the mind and mind pursued by education.Keywords: Doctor Abdul Rivai, STOVIA, Bengkulu City